Las constituciones de 1812 - Paladines, Carlos (2014)
The following seven articles are the result of the celebration of the "Bicentary of Cadiz Constitution Commemorative sessions/days" in October 2012.  This publication contains a depth analysis of the circumstances which surrounded the promulgation of the liberal Constitution of Spain in 1812 including the significance and consequences for the Spanish America. A comprehensive study of the situation in the former Audiencia de Quito (cursivas) has been made. Political, social, economic and regional aspects during the first quarter of the XIX Century which had a great influence in the development of the modern Ecuador  have been analysed.